Getting to the Heart of the Planetary Health Movement: Nursing Research Through Collaborative Critical Autoethnography - Jessica LeClair; De-Ann Sheppard; Robin Evans-Agnew (Challenges)
Humans and more-than-humans experience injustices related to the triple planetary crisis of climate change, pollution, and biodiversity loss. Nurses hold the power and shared Responsibility (Note on Capitalization: Indigenous Scholars resist colonial grammatical structures and recognize ancestral knowledge by capitalizing references to Indigenous Ways of Knowing (Respect, Relations, and Responsibilities are capitalized to acknowledge Indigenous Mi’kmaw Teachings of our collective Responsibilities to m’sit no’ko’maq (All our Relations). Respect for Land, Nature, Knowledge Keepers, Elders, and the names of Tribes, including the Salmon People and sacred spaces, such as the Longhouse, are also denoted with capitals)) to support the health and well-being of each other and Mother Earth. The heart of the Planetary Health movement to address these impacts centers on an understanding of humanity’s interconnection within Nature. As nurses, we seek partnerships with more-than-human communities to promote personal and collective wellness, Planetary Health, and multispecies justice. This article introduces a longitudinal, collaborative autoethnography of our initial engagement with more-than-human communities. In this research, we utilize reflexive photovoice and shared journals to describe our early conversation about this interconnection with three waterways across diverse geographies. This work acknowledges the importance of relational and embodied Ways of Knowing and Being. We invite nurses to embrace the heart of the Planetary Health movement and share these stories with their more-than-human community partners.